SETTLEMENT OF DEFAULTS IN THE LIFE INSURANCE POLICY BETWEEN THE INSURER AND THE INSURED - Aswin; Suhendro; Indra Afrita (JILPR Journal Indonesia Law and Policy Review, 2021)
When the policy holder or insurance participant or the insured experiences a disaster or suffers a loss or damage as stated in the contract, the insured has the right to file an insurance claim. The recipient of this insurance is not only the insured whose name is listed as the policy holder of the insurance company but can also be another person appointed directly by the insured. The formulation of the problem in this study is the Default in the Life Insurance Policy between the Insurer and the Insured, howSettlement of Defaults in Life Insurance Policies Between the Insurer and the Insured and What are the Legal Consequences for Settlement of Defaults in a Life Insurance Policy between the Insurer and the Insured. The purpose of this research is to analyze Default in a Life Insurance Policy between the Insurer and the Insured, To Analyze Settlement of Defaults in Life Insurance Policies Between the Insurer and the Insured To Analyze Legal Consequences Settlement of Defaults in Life Insurance Policies Between the Insurer and the Insured.This research method is normative legal research. The conclusions in this study have answered the problems that arise, namely:Default in a Life Insurance Policy between the Insurer and the Insured that a life insurance agreement is made between the policy holder and the insurer, with the consequence that the policy holder pays the premium and the insurer provides risk protection to the policy holder and/or the insured within a certain time as stipulated in the agreement. Default can be done by the policyholder, one of which is by not paying life insurance premiums until the grace period ends.Settlement of Defaults in Life Insurance Policies Between the Insurer and the Insured that The insurer and the insured binding themselves in the insurance agreement must be in accordance with the provisions of the applicable laws and regulations, which are contained in Article 1338 Paragraph (1) of the Civil Code. This provision states that when the agreement has been agreed by both parties, then the agreement will apply as a law that will bind the parties therein. Because of lawSettlement of Defaults in Life Insurance Policies Between the Insurer and the Insured that if the premium is not paid by the policyholder, the life insurance agreement can be canceled by law and the policy will be canceled or called lapsed, namely the termination of insurance coverage as a result of not paying premiums until the insurance contract period ends and the premiums that have been paid will not be returned.